(untitled) - 1956-; Reinhold, Judge; 1937-; Holliday, Polly; 1948-; Dante, Joe; 1946-; Spielberg, Steven (Burbank, CA, 2007)
When a young bank teller inadvertently breaks the rules of Mogwai care, his new pet Gizmo multiplies into a bevy of mischievous brothers, who soon morph into malevolent scaly creatures.
Keywords: Monsters; Drama; Families; Drama; Video recordings for the hearing impaired; Horror films; Feature films; Fantasy films; Comedy films